Dietary Galla Chinensis tannic acid supplementation in the diets improves growth performance, immune function and liver health status of broiler chicken - Niu, Jiaxing; Wang, Qinjin; Jing, Changwei; Liu, Yang; Liu, Hua; Jiao, Ning; Huang, Libo; Jiang, Shuzhen; Guan, Qinglin; Li, Yang; Yang, Weiren (Frontiers in Veterinary Science, 2022)
This experiment was conducted to investigate the effects of Galla Chinensis tannic acid (TA) on growth performance, immune function, and liver health status in broilers. A total of 288 1-day-old Arbor Acres broiler chickens were randomly divided into two groups in a 42-days study. The two groups were a basal diet (CON group) and a basal diet supplemented with 300 mg/kg Galla Chinensis tannic acid (TA group). The results showed that the TA group had significantly decreased feed-to-gain ratio (F/G) throughout the experiment (P < 0.05). The levels of total protein, albumin, low density lipoprotein, high density lipoprotein, urea, total cholesterol, and glucose in the TA group were significantly higher than in the CON group (P < 0.05). In addition, the serum immunoglobulin G, immunoglobulin M, and complements (C3, C4) levels in the TA group were significantly higher than those in the CON group (P < 0.05). Compared with the CON group, the hepatic interleukin-6, interleukin-18, NLRs family pyrin domain containing 3 (NLRP3), caspase-1, and caspase-3 in the TA group were significantly decreased (P < 0.05). Besides, TA group had significantly lower mRNA expression levels of toll-like receptor 4 (TLR4), myeloid differentiation primary response 88 (MyD88), nuclear factor-kappa B (NF-κB), and NLRP3 in liver (P < 0.05). The TA group had significantly higher the mRNA expression levels of Bcl-2 than CON group in liver (P < 0.05). Moreover, TA group tended to decrease Bax/Bcl-2 ratio in liver (P < 0.10). To sum up, dietary supplemented with microencapsulated TA from Galla Chinensis had beneficial effects on growth performance, immune function, and liver health status in broilers. The protective role of TA from Galla Chinensis in liver health of broilers might be related to the inhibition of hepatic apoptosis and pyroptosis via inactivation of TLR4/MyD88/NF-κB signaling pathway.